Hubungan Pengetahuan Ibu Tentang Penatalaksanaan Diare dengan Kejadian Diare Pada Anak Balita di Wilayah Kerja Puskesmas Pucangsawit surakarta - Lamaira, Rosmala (2016)
Background: Diarrhea is a major cause of death of children aged less than five years (toddler) globally. It has been estimated that every 30 seconds one child dies and about 2000 toddlers die cause of diarrhea. Many factors can influence the incidence of diarrhea such as host environment, behavior, health service, and knowledge. The knowledge is essential to establish the behavior in the community. The better knowledge of the mother, it is expected that mother can understand well about the treatment of diarrhea. Purpose: The research was carried out to determine the correlation between maternal knowledge about the treatment of diarrhea with the incidence of diarrhea in toddler in Pucangsawit Public Health service working area of Surakarta. Method: The type of this research is analytic observational, withpuposive sampling technique. Result: The data were analysed by using chi square test. Based on the chi-square test showed that p-value = 0,009 (p < 0,05), it means that there is a correlation between mother's knowledge about the management of diarrhea with the incidence of diarrhea. Conclusion: Based on the analysis test, there is a significant association between maternal knowledge about the treatment of diarrhea with the incidence of diarrhea in toddler in Pucangsawit Public Health service working area of Surakarta